An Unprecedented Revolution in Medicinal Chemistry Driven by the Progress of Biological Science - Chou, Kuo-Chen (Current Topics in Medicinal Chemistry, 2017)
The eternal or ultimate goal of medicinal chemistry is to find most effective ways to treat various diseases and extend human beings’ life as long as possible. Human being is a biological entity. To realize such an ultimate goal, the inputs or breakthroughs from the advances in biological science are no doubt most important that may even drive medicinal science into a revolution. In this review article, we are to address this from several different angles.
Keywords: Encephalomyopathy